Basic competency for Elementary School teachers in teaching music - Widodo, Tri Wahyu; Cross, Natasha Fabio (FBSB UNY, 2023)
Competence is a skill that everyone must possess to complete various tasks. With constantly evolving work challenges, competencies must always follow the dynamics of the development of job challenges. This study revealed the phenomenon of the profession of a class teacher in elementary school education, which has significant challenges in the teaching and learning process and is a big concern for the government. Therefore, understanding the phenomenon of teachers as an educator profession is very important in understanding how to design and increase the professional competence of classroom teachers in musical instruments, such as recorders. The research will focus on the class teacher who teaches the art of music through recorders at the elementary school in the field of art knowledge, particularly the music arts. This study explores the problems of how classroom teachers achieve essential competencies to teach music knowledge. The data collected results from observations of classroom teacher training on music art learning organized in collaboration between Yamaha Education and the Ministry of Education and Culture in 2022. In training to improve the competence of class teachers, many need to be revealed and need solutions. So, this study aims to design various things that can improve the competence of elementary school class teachers in providing knowledge of music art. This study's data collection and analysis method uses a qualitative tradition through a case study approach for elementary school teachers. Keywords: teacher competence, elementary school, music arts, recorder